The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s005950070036
|View full text |Cite
|
Sign up to set email alerts
|

A decreased serum concentration of nitrite/nitrate correlates with an increased plasma concentration of lactate during and after major surgery

Abstract: A decrease in the production of nitric oxide (NO) due to surgical stress has been reported. We investigated whether this decrease in NO production was related to cytokine induction and/or other clinical parameters. We therefore measured the concentrations of serum nitrite/nitrate (a stable end product of NO), serum interleukin (IL)-6, and standard clinical parameters in 13 patients undergoing major upper abdominal and thoracoabdominal surgery at preanesthesia (PRE), 2h after a surgical incision (2H), at the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Reported results in these studies are inconsistent, with either no perioperative differences detected in MDA and NO (Ozmen et al 2002 , McHoney et al 2005 ) or increased MDA intraoperatively, with reductions in NO during surgery and up to day-1 thereafter (Zulfikaroglu et al 2002 , Bukan et al 2004 ). Data from investigations during major upper gastrointestinal surgery, however, found consistent reductions in NO production (Satoi et al 1998 , Fujioka et al 2000 ) supporting our findings. In addition to these, cGMP (a downstream messenger in the NO signalling pathway) was measured in our cohort, which showed a perioperative decline.…”
Section: Discussionsupporting
confidence: 90%
“…Reported results in these studies are inconsistent, with either no perioperative differences detected in MDA and NO (Ozmen et al 2002 , McHoney et al 2005 ) or increased MDA intraoperatively, with reductions in NO during surgery and up to day-1 thereafter (Zulfikaroglu et al 2002 , Bukan et al 2004 ). Data from investigations during major upper gastrointestinal surgery, however, found consistent reductions in NO production (Satoi et al 1998 , Fujioka et al 2000 ) supporting our findings. In addition to these, cGMP (a downstream messenger in the NO signalling pathway) was measured in our cohort, which showed a perioperative decline.…”
Section: Discussionsupporting
confidence: 90%
“…A small number of previous studies have investigated NO Bukan et al, 2004). Data from investigations during major upper gastrointestinal surgery however, found consistent reductions in NO production (Satoi et al, 1998, Fujioka et al, 2000 supporting our ndings. In addition to these, cGMP (a downstream messenger in the NO signalling pathway) was measured in our cohort, which showed a perioperative decline.…”
Section: Discussionsupporting
confidence: 88%
“… 11 evaluated NO metabolism following major elective surgery, and demonstrated that plasma nitrate and nitrite levels had a biphasic response in which they decreased early after surgery and normalized by POD 7. Decreased circulating nitrate and nitrite levels have also been observed early after thoracoabdominal 12 or hepato‐pancreato‐biliary surgery 13 . Contradictory to these observations, Arias‐Diaz et al.…”
Section: Discussionmentioning
confidence: 98%